2016
DOI: 10.1186/s40942-016-0047-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for diabetic retinopathy: a case–control study

Abstract: BackgroundDiabetic retinopathy (DR) is the major cause of blindness among working age adults. The aim of the study was to investigate risk factors for development of DR.MethodsA case–control study was performed based on data from 240 individuals (80 cases and 160 controls) attending the Outpatient Specialty Clinic of the University of South Santa Catarina (UNISUL), between Mar/2010 and May/2014. Data collection occurred through review of medical charts for presence or absence of DR, determined by an ophthalmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
35
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 56 publications
(84 reference statements)
10
35
0
10
Order By: Relevance
“…DWR and DR patients were matched according to age, BMI, and lipid profile, thereby ruling out the contribution of obesity [11] or lipotoxicity [33,34] to DR. In addition, significant differences between both T2DM patient groups were seen in the age of onset and duration of diabetes, and HbA1c, confirming the role of long exposure to hyperglycemia and poor glycemic control to DR [24,[34][35][36]. This appears to influence DR severity, as higher sCD40L levels were seen in PDR more so than NPDR patients, which is likely attributed to hyperglycemia and insulin resistance (HOMA-IR) [18].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…DWR and DR patients were matched according to age, BMI, and lipid profile, thereby ruling out the contribution of obesity [11] or lipotoxicity [33,34] to DR. In addition, significant differences between both T2DM patient groups were seen in the age of onset and duration of diabetes, and HbA1c, confirming the role of long exposure to hyperglycemia and poor glycemic control to DR [24,[34][35][36]. This appears to influence DR severity, as higher sCD40L levels were seen in PDR more so than NPDR patients, which is likely attributed to hyperglycemia and insulin resistance (HOMA-IR) [18].…”
Section: Discussionmentioning
confidence: 80%
“…Insofar as sCD40L levels are generally elevated in obesity [29,30], our findings indicate that sCD40L levels did not correlate with BMI in DR patients, as well as NPDR and PDR groups. This suggests that the increases in sCD40L levels in DR patients are the result of impaired glucose tolerance associated with inflammatory changes [24,31,32], independent of obesity. DWR and DR patients were matched according to age, BMI, and lipid profile, thereby ruling out the contribution of obesity [11] or lipotoxicity [33,34] to DR.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Garcia et al (2003); Pérez et al (2011). Moreno et al (2013); ACP (1999); Boelter et el (2003); DCCT Research Group (2005); Bosco et al (2005); ACP (1999); Lima et al (2016). Nefropatia diabética Klein et al (1984); Boelter (2003); Reggi et al (2001).…”
Section: Methodsunclassified
“…11 Some studies reported the higher incidence of DR with obesity. 12,13 While some studies observed a decreased incidence of DR in higher BMI individuals 14,15 and still few other studies noticed an insignificant association between obesity and the occurrence of DR. 16 In order to find the trend in local population we explored the comparison and correlation in type two diabetics with and without diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%